Prevalence of exercise-induced bronchospasm among athletes in the hot and humid climate of brazzaville, Congo - Nsompi, Florent; Messan, Folly (My University, 2019)
This study aims to determine the prevalence of EIB in high-level Congolese athletes acclimated to hot and humid air conditions. Materials and Methods: The study involved 18 high-level athletes training in an environment relatively polluted. The stress test consisted of a continuous running treadmill warm-up set at 7.5 km. h-1, followed by an endurance race incremented by 1.5 km. h-1 every 3 minutes until exhaustion. Respiratory function examinations were performed at rest, at the end of the exercise test and at 5-minute increments for 25 minutes. For each modality, the EIB diagnosis was based on an average reduction of at least 10% in the first-second forced expiratory volume (FEV1). The subjects who presented this criterion were declared sensitive to bronchospasm and constituted the EIB (+) subgroup, while those that were not identified as such were considered non-susceptible and constituted the EIB (-) subgroup.
Keywords: Prevalence; Exercise; Bronchospasm; Hot and humid climate; Congo